Elaboração da interpretação automática de fraturas nos perfis de imagem utilizando a Inteligência Artificial - Almeida Conrado, Victoria; Gomes dos Santos Ribeiro, Mariléa (Latin American Journal of Energy Research, 2023)
Artificial Intelligence (AI) is a data processing approach that uses information analysis, pattern detection and predictions with little human intervention. The field of AI encompasses several subsets, with emphasis on machine learning (ML), which has great potential in the oil and gas industry, especially in data analysis and interpretation. ML algorithms such as Support Vector Machine (SVM), Artificial Neural Networks (ANN), Deep Learning (DL) and Genetic Algorithms (GA) have been successfully applied in the oil industry. The petroleum industry faces significant technological challenges, given its complexity. Geological formation analysis through logging is crucial to improve the assessment of rock formations, minimize damage and reduce costs when drilling wells. Furthermore, the identification of natural and induced fractures is fundamental to understanding reservoirs, especially non-disruptive ones. The study of fractures can be divided into qualitative and quantitative aspects, which involves the identification and detailed analysis of fractures in reservoirs. AI, especially ML, can be applied to analyze the geometry, orientation, density and complexity of fractures, classifying them into different types such as induced and natural fractures. The objective of this study is to automate the interpretation of flaws in image profiles through the use of Artificial Intelligence, improving the efficiency, accuracy and speed of this procedure. The Python programming language and the Jupyter Notebook tool were used to develop the AI program. Data and images were collected, which were processed and analyzed using libraries such as OpenCV, Numpy and Sklearn.svm. The results obtained demonstrate the effectiveness of AI in identifying fractures in different types of image profiles, including acoustic images, resistivity images, and other logging tools. Artificial Intelligence was able to accurately identify natural fractures, low-amplitude fractures, internal fractures and other geological events. However, the success of AI depends on the quality and quantity of training data, and challenges such as geological complexity and image resolution still need to be overcome. The application of AI in the automatic interpretation of fractures in images in the petroleum industry offers significant improvements in the efficiency and speed of the process, contributing to the understanding of the characteristics of rock formations.
Keywords: Artificial Intelligence; Machine Learning; Oil and Gas; Fractures; Automatic Interpretation; Image Processing; Support Vector Machine (SVM)